2010
DOI: 10.1093/neuonc/noq147
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and safety of TRAIL-producing human adipose tissue-derived mesenchymal stem cells against experimental brainstem glioma

Abstract: Mesenchymal stem cells (MSCs) have an extensive migratory capacity for gliomas, which is comparable to that of neural stem cells. Among the various types of MSCs, human adipose tissue-derived MSCs (hAT-MSC) emerge as one of the most attractive vehicles for gene therapy because of their high throughput, lack of ethical concerns, and availability and ease of isolation. We evaluated the therapeutic potential and safety of genetically engineered hAT-MSCs encoding the tumor necrosis factor-related apoptosis-inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 35 publications
2
62
0
Order By: Relevance
“…MiR-34 restoration also significantly inhibites the self-renewal at the site of tumors. 75 It has been shown that TRAIL-expressing MSCs can significantly inhibit tumor growth and induce significant survival benefits in animal models; 76,77 moreover, MSCs expressing TRAIL can cause apoptosis or death and reduce colony formation of SP cells in quamous (H357) and lung (A549) cancer cell lines and act in synergy with conventional chemotherapy. 78 The sensitivity of cancer stem-like cells to TRAIL is various may be due to their different genetic background.…”
Section: Micrornasmentioning
confidence: 99%
“…MiR-34 restoration also significantly inhibites the self-renewal at the site of tumors. 75 It has been shown that TRAIL-expressing MSCs can significantly inhibit tumor growth and induce significant survival benefits in animal models; 76,77 moreover, MSCs expressing TRAIL can cause apoptosis or death and reduce colony formation of SP cells in quamous (H357) and lung (A549) cancer cell lines and act in synergy with conventional chemotherapy. 78 The sensitivity of cancer stem-like cells to TRAIL is various may be due to their different genetic background.…”
Section: Micrornasmentioning
confidence: 99%
“…[29][30][31] MSCs expressing TRAIL exhibited short-and long-term therapeutic effects without significant complications in glioma. [32][33][34][35] But there was no report about TRAIL gene modified MSCs (TRAIL-MSCs) in the therapy of HCC. As mentioned above, HCC cells showed high resistance to TRAIL, so TRAIL-MSCs alone might be difficult to achieve desired effect.…”
Section: Resultsmentioning
confidence: 99%
“…These factors make TRAIL an attractive genetic tool for use in the treatment of tumors. Choi et al (2011) were the first to demonstrate short-and long-term therapeutic efficacies using TRAIL-producing human AT-MSCs. Their study included both in vitro and in vivo experiments.…”
Section: Msc Delivery Of Therapeutic Genesmentioning
confidence: 99%